Knowledge, Attitude and Practice Towards Insulin-Self Administration Among Diabetic Patients Attending Bedele Hospital, Southwest Ethiopia, 2019/2020 - Fego MW (Dove Medical Press, 2021)
Melese Workneh Fego,1 Jihad Tahir Yasin,2 Gezahegn Mamo Aga2 1Department of Nursing, College of Public Health and Medical Sciences, Mettu University, Mettu, Ethiopia; 2Mettu Health Science College, Mettu, EthiopiaCorrespondence: Melese Workneh FegoMettu University, PO Box: 318, EthiopiaEmail meleseworknehfego@gmail.comBackground: Diabetes mellitus is a heterogeneous clinical syndrome secondary to defects in insulin secretion, action, or both. The worldwide fatality and disability rate imposed diabetic patients for insulin self-administration regardless of a scarcity of their knowledge, attitude, and practices. Thus, the study aimed to assess knowledge, attitude, and practice towards insulin-self administration among diabetic patients attending Bedele Hospital, southwest of Ethiopia.Methods: A facility-based cross-sectional study was conducted by a consecutive sampling technique at Bedele Hospital from 15 December 2019 to 22 January 2020. A pretested structured English version relevant questionnaire translated to local language was administered on 196 subjects. Data were tested for clarity, consistency and analyzed using The Statistical Package for Social Sciences version 23 and summarized using descriptive statistics in the form of tables and figures.Results: Of 196 subjects, 180 subjects participated in the study giving a response rate of 92%. The study reveals that knowledge, attitude, and practice towards insulin self-administration were 132 (67.3%), 113 (57.6%), and 123 (62.8%), receptively, which implies that good knowledge, a favorable attitude, and good practice to insulin self-administration.Conclusion: While the patients had good knowledge, good practice, and a favorable attitude to insulin self-administration, it does not match sufficient thus, to achieve a maximum level the hospital should develop several strategies like constant information education communication.Keywords: attitude, diabetic patients, insulin self-administration, knowledge, practice